1999
DOI: 10.1159/000031055
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Hemolysis and Lipid Peroxidation in Blood during Storage in the Presence of Nicotinic Acid

Abstract: Background and Objectives: There is increase in lipid peroxidation with consequent increase in hemolysis when blood is stored in di–(2–ethyl hexyl)phthalate (DEHP) plasticized bags. Studies carried out by us and others have indicated the ability of red cells to synthesize NAD+ from added nicotinic acid. Apart from the role of NAD+ in glycolysis, NADPH is required for reduction of oxidized glutathione to its reduced form by glutathione reductase. Reduced glutathione is an important antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
(10 reference statements)
0
11
0
Order By: Relevance
“…During storage of RCC, up to 50 percent of the extracellular Hb may eventually be contained within vesicles 32 . In contrast to the Hb inside vesicles, which is rapidly removed from the circulation, 33 free Hb can be harmful, due to autoxidation and generation of free radicals 34 . Because the LDH assay only measures free extracellular LDH, the LDH level may constitute a more meaningful indicator for RBC lysis than the so‐called hemolysis based on extracellular Hb.…”
Section: Discussionmentioning
confidence: 99%
“…During storage of RCC, up to 50 percent of the extracellular Hb may eventually be contained within vesicles 32 . In contrast to the Hb inside vesicles, which is rapidly removed from the circulation, 33 free Hb can be harmful, due to autoxidation and generation of free radicals 34 . Because the LDH assay only measures free extracellular LDH, the LDH level may constitute a more meaningful indicator for RBC lysis than the so‐called hemolysis based on extracellular Hb.…”
Section: Discussionmentioning
confidence: 99%
“…RBC storage under conventional conditions is considered an oxidative stress for RBCs, as evidenced by increases in reactive oxygen species over time [77], accumulation of oxidative biomarkers, including malondialdehyde [78] and oxidation products of human serum albumin [79], as well as oxidationdependent alterations of RBC membrane proteins, such as spectrin [80]. Further evidences implicating oxidative stress in the adverse effects of storage on RBCs include improvements in the storage lesion, in post-transfusion survival [81] and in storage-related protein processing [82], when RBCs are stored under anaerobic conditions, when antioxidants are administered to blood donors prior to donation [83] and when blood is stored in the presence of antioxidants [84].…”
Section: Rbc Transfusionmentioning
confidence: 99%
“…During storage of whole blood (WB) in CPDA (citrate–phosphate–dextrose–adenine) [1] and of red blood cells (RBCs) in SAGM (saline–adenine–glucose–mannitol) [1], there is a dramatic decrease in the concentration of 2,3‐diphosphoglycerate (2,3‐DPG) in the RBCs, resulting in a significantly lower delivery of oxygen to the tissues. During our previous study of a large number of blood or RBC samples, the level of 2,3‐DPG was found to decrease from 12–15 µmol/g of haemoglobin (Hb) on day 1 to very low values (for instance, 0·46–1·3 µmol/g of Hb) on day 28 [2,3]. 2,3‐DPG is produced during glycolysis, by the diphosphoglycerate shunt pathway [4], from 1,3‐diphosphoglycerate (1,3‐DPG) via the action of the enzyme 2,3‐DPG mutase.…”
Section: Introductionmentioning
confidence: 99%